Endovascular Treatment of Chronic Total Occlusion in the Subclavian Artery: A Review of 23 Cases - Niu, Guochen; Yan, Ziguang; Zhang, Bihui; Yang, Min (Frontiers in Neurology, 2020)
Objectives & Background: To review technical details and long-term outcomes of endovascular treatment of chronic total occlusion (CTO) of the subclavian artery. Methods: From January 2010 to May 2017, 23 patients (17 male; median age, 65 years) underwent endovascular treatment for CTO of the subclavian artery. All lesions had been diagnosed by duplex scanning or computed tomography angiography before treatment. Sixteen (70.0%) patients had symptoms of vertebrobasilar insufficiency, 6 (26.1%) patients had symptoms of arm ischemia, and 2 (8.7%) patients were asymptomatic. Duplex scanning revealed that 16 patients had grade 3 and 6 patients had grade 2 steal blood flow. After recanalization, lesions were treated by stenting. Patients were followed up at 1, 3, 6, and 12 months after endovascular treatment, and annually thereafter. Results: The overall technical success rate was 91.3% (21/23). The successful recanalization rate of antegrade and retrograde approaches were 68.2% (15/22) and 75.0% (6/8), respectively. The rate of clinical symptom remission was 95.2% (20/21) after treatment. No perioperative death or permanent neurological deficits were observed. One patient had arterial dissection treated by covered stent. The estimate cumulative primary and secondary patency rates at 5 years were 74.6% and 78.8%, respectively. Conclusion: Endovascular treatment is a feasible and safe treatment for CTO lesions of the subclavian artery.